النموذج الديناميكي لتداخلات الرنين الصوتي في أنظمة الاحتراق - محمود حبيب (Latakia University Journal -Engineering Sciences Series, 2019)
في عمليات الاحتراق المستمر، غالبا ما يوجد تداخل واقتران ما بين انطلاق الحرارة و ذبذبات الضغط التي تقود إلى شكل من الرنين يُعرف بعدم الاتزان الصوتي الحراري. إن وجود عدم الاتزان هذا في أنظمة الاحتراق العملية يشكل خطرا على سلامة بنيتها، ويكون هذا الخطر متناسباً مع سعة ذبذبات الضغط، إذ يتراوح تأثيرها بين تراجع في مستوى أداء منظومة الاحتراق (نقاط موضعية عالية الحرارة، وانخفاض فعالية الاحتراق) وصولا إلى حد إخفاق المجموعة بسبب تصدعات في بنيتها. غير أن المنظم الفعال ذا التغذية العكسية يمكن أن يُسهم في تجنيب مجموعة الاحتراق لهذه المشكلات، إذ يستخدم لاكتشاف بداية نشوء هذه الذبذبات وتطورها وبشكل ملائم يقوم بتعديل مؤشرات الدخل. ولكن حتى يتم توفير الخطوط الأولية الواضحة والمرشدة لتصميم مثل هذا المنظم لا بد من توفير الإطار الرياضي التحليلي لدراسة عدم الاتزان بالإضافة إلى تفاصيل التأثيرات المتبادلة بين المتحولات الأساسية لعملية الاحتراق. في هذا البحث نقدم النتائج الأولية التي تمكنّا من الحصول عليها نتيجة للجهد المتواصل بهدف تطوير نموذج رياضي نظامي لهذه الظاهرة. هذا الجهد يتعلق بتطوير نموذج تغذية عكسية لحارق مسبق الخلط، وقد تم اشتقاق هذا النموذج باستخدام معادلات الحفظ الأساسية لجريان أحادي البعد، وبُني بشكل أساسي على النموذج الديناميكي للهب. إن النموذج الذي تم الحصول عليه لا يسلط الضوء فقط على سلوكية عدم الاتزان الصوتي الحراري، لكنه يؤمن أيضا طريقة لتحديد العلاقة ما بين عدم الاتزان والمؤشرات الفيزيائية المختلفة. ولإيضاح دقة النموذج المقترح تمت مقارنة نتائجه بالنتائج التجريبية لأبحاث سابقه. In continuous combustion processes, often there are a coupling and interaction present between the heat release and pressure oscillations which leads to a form of resonance referred to as thermoacoustic instability. The presence of this instability in a practical devices can endanger the structural integrity of the system, and this danger is proportional to the pressure oscillations amplitude. The effect of this instability ranges from system performance degradation (high local hot spots, reduced combustion efficiency) and, in the worst case, system failure due to structural damage. An active feedback controller offers help in this regard, since it could be employed to detect the onset of these growing oscillations and appropriately modulate the input sources. In order to provide clear guidelines for the design of such controller, an analytical framework for studying the instability as well as the details of the interactions between the key process variables must be provided. In this paper, we present the preliminary results obtained from our efforts to develop such a systematic framework. These pertain to the development of a feedback model of a premixed combustor which is derived using the conservation equations of one-dimensional flow dynamics and a fundamentally based flame dynamics model. We show that this feedback model sheds light not only on the thermoacoustic instability behavior, but also provides a way of quantifying the relation between the instability and the physical parameters. A simple numerical example is used to illustrate the accuracy of the proposed model and is compared with experimental results reported in the literature.